Intra-cervical lymphatic immunotherapy for dust mite-induced allergic rhinoconjunctivitis in children: a 3-year prospective randomized controlled trial - Wang, Qixing; Wang, Kai; Qin, Yang; Huang, Weijun; Li, Yin; Yu, Qingqing; Xiong, Yu; Guo, Yingwei; Zheng, Rui; Tang, Jun (Frontiers in Immunology, 2023)
Background Pediatric allergic rhinoconjunctivitis has become a public concern with an increasing incidence year by year. Conventional subcutaneous immunotherapy (SCIT) has long treatment time, high cost and poor compliance. The novel immunotherapy significantly shortens the course of treatment by directly injecting allergens into cervical lymph nodes, which can perform faster clinical benefits to children. Objective By comparing with SCIT, this study aimed to evaluate the long-term efficacy and safety of intra-cervical lymphatic immunotherapy (ICLIT). Methods This is a prospective randomized controlled study. A total of 50 allergic rhinoconjunctivitis children with dust mite allergy was randomly divided into ICLIT group and SCIT group, receiving three cervical intralymphatic injections of dust mite allergen or three years of subcutaneous injection, separately. Primary outcomes included total nasal symptom scores (TNSS), total ocular symptom scores (TOSS), total symptom scores (TSS), total medication scores (TMS), and total quality of life score. Secondary outcomes included pain perception and adverse reactions during treatment. Other secondary outcome was change in Dermatophagoides pteronyssinus (Derp) and Dermatophagoides farina (Derf) -specific IgE level. Results Both groups had significantly decreased TNSS, TOSS, TSS, TMS, and total quality of life score after 36 months of treatment (p<0.0001). Compared with SCIT, ICLIT could rapidly improve allergic symptoms (p<0.0001). The short-term efficacy was consistent between the two groups (p=0.07), while the long-term efficacy was better in SCIT group (p<0.0001). The pain perception in ICLIT group was lower than that in SCIT group (p<0.0001). ICLIT group was safer. Specifically, the children had only 3 mild local adverse reactions without systemic adverse reactions. The SCIT group had 14 systemic adverse reactions. At last, the serum Derp and Derf-specific IgE levels in ICLIT and SCIT groups decreased 3 years later (p<0.0001). Conclusion ICLIT could ameliorate significantly the allergic symptoms in pediatric patients with an advantage in effectiveness and safety, besides an improved life quality including shortened period of treatment, frequency of drug use and pain perception. Clinical trial registration https://www.chictr.org.cn/, identifier ChiCTR1800017130.